Tsukamurella pulmonis conjunctivitis in patients with an underlying nasolacrimal duct obstruction – report of two cases. Issue 2 (9th February 2021) - Kechker, Peter; Senderovich, Yigal; Ken-Dror, Shifra; Laviad-Shitrit, Sivan; Halpern, Malka
Abstract : Tsukamurella pulmonis ( Actinobacteria ), a Gram-positive, obligate aerobic and weakly or variably acid-fast bacterium, is an opportunistic pathogen. Here we report two cases of conjunctivitis caused by T. pulmonis . Both patients had a previous history of nasolacrimal duct obstruction (NLDO). Isolation of T. pulmonis was performed on chocolate, tryptic soy blood and Columbia nalidixic agars. After 24 h of incubation, odourless, white-greyish, membrane-like colonies were observed. The VITEK-2 bacterial identifier system failed to identify the species, while Vitek-MS matrix-assisted laser desorption ionization time-of-flight technology, successfully identified the isolate from case 2 but not from case 1. Final identification was verified using 16S rRNA gene sequencing. An antibiogram was performed and according to the results cefazoline in addition to vancomycin eye drops for 5 days, were suggested as a treatment in case 1. In case 2 the infection was ended without treatment. This is the first report of Tsukamurella as a pathogen that causes conjunctivitis in patients with NLDO.